Biomarkers of acute kidney injury in the intensive care unit - Md Ralib, Azrina (Malaysian Society of Anaesthesiology, 2014)
Acute Kidney Injury (AKI) is common in critical illness, and contributes to high mortality. Current consensus AKI definition is mainly based on functional biomarkers, plasma creatinine and urine output. Emerging studies showed the utility of structural biomarkers for earlier detection of AKI, and stratification of injury severity. A combination of these functional and structural biomarkers is of utility for risk stratification and prediction of outcome. This paper provides an overview of AKI with emphasis on critically ill patients. The major focus is on the early detection of AKI and prediction of outcome by functional and structural biomarkers. The future advances in the use of AKI biomarkers are explored.